The Role of Self-Efficacy in Predicting Academic Buoyancy Among Working Students in Higher Education - Evi Safitri; Kus Candra Gunawan; Tia Rahmania (LPPM STKIP Kusuma Negara, 2026)
Students who work while pursuing higher education face dual demands that potentially induce academic stress and affect their capacity to navigate daily scholastic challenges. In this context, academic buoyancy emerges as a crucial aspect that helps students maintain academic engagement and adaptively overcome learning barriers. However, research examining academic buoyancy among working students in Indonesia remains relatively limited. This study aims to analyze the influence of self-efficacy on academic buoyancy among working students at a private university in Indonesia. Utilizing a quantitative approach, this study employed a correlational design and simple linear regression analysis. Participants consisted of 103 working students selected through a purposive sampling technique. Self-efficacy was measured using the General Self-Efficacy Scale, while academic buoyancy was assessed based on the Martin and Marsh framework. The results demonstrated that self-efficacy has a positive and significant effect on academic buoyancy (beta = 0.399; p < .001). The coefficient of determination (R² = 0.159) indicates that self-efficacy explains 15.9% of the variance in academic buoyancy. These findings confirm that belief in one's capabilities plays a vital role in helping working students manage academic pressures; Therefore, efforts to enhance academic buoyancy should prioritize strengthening self-efficacy while reinforcing social support through peer support and university counseling programs, thereby enabling working students to better cope with academic challanges.